Aplicação do incentivo financeiro do PMAQ, no 3º ciclo, sob a ótica das equipes de saúde e sua influência na qualificação da atenção básica nos municípios da Paraíba - Lins, Adriana da Silva Baltar Maia (2021)
In the Unified Health System, Primary Care predominantly operates in the logic of the Family Health Strategy, characterized by its scope and proximity to the territories, as well as the dynamics of population organization. The health teams are formed by several professional categories and some have the support of the extended Family Health Center (NASF). Considering the advances and challenges regarding the strengthening of Primary Care, the Program for Improving Access and Quality of Care (PMAQ) was created in order to assess the quality of health services, based on the performance of Primary Care professionals in the achievement of pre-established goals, aiming at the reorganization of the health network. The present dissertation aimed to analyze the understanding of the health team professionals about the application of the financial incentive of the PMAQ and its influence on the qualification of Primary Care in the municipalities of Paraíba, considering that most of the actions are developed by them. In this work, the secondary research database entitled ‘Impacts of PMAQAB in Primary Care: analysis of the application of the financial incentive for performance to health teams in Brazil’, built by researchers from the Political Research, Education and Research Group, was used. Health Care - GPECS at UFPB, based on a questionnaire answered by workers from the Primary Care health teams in the municipalities of the state of Paraíba, in the 3rd cycle of the PMAQ. The sample consists of 812 professionals who were interviewed simultaneously with the external evaluation in 2018. For the study, 5 structuring axes were considered for qualified Primary Care, improved access, improved efficiency, improved health results, better user satisfaction and better satisfaction of professionals. It was a cross-sectional, descriptive study with a quantitative approach. The statistical approach involved descriptive data analysis and logistic regression modeling to assess how the use of PMAQ-AB resources influenced the perception of the quality of primary care in the municipalities of Paraíba. The results show that, although the PMAQ was a program that sought the qualification of Primary Care, linking a broad view in the evaluation aspects, most of the professionals participating in the study, pointed out that to obtain an improvement in the quality of Primary Care, it would be relevant to take into consideration essentially issues related to wages. The results of the logistic regression models indicated that there was a consensus on the part of the different professional categories that the guarantee of a good salary remuneration results in a better provision of services and, therefore, indicate an improvement in quality in terms of access, efficiency, in health, work process, health results, user and professional satisfaction. It was clarified with this study that the PMAQ had relevant aspects about evaluation processes, in the search for financial increase to improve the quality of care in Primary Care, requiring a better understanding by professionals of the Primary Care guidelines, as well as of what the program was aiming at, to improve effectiveness in the quality of assistance.